Pre-flight testing of preterm infants with neonatal lung disease: a retrospective review. Issue 4 (31st January 2006) - Udomittipong, K; Stick, S M; Verheggen, M; Oostryck, J; Sly, P D; Hall, G L
Abstract : Background: The low oxygen environment during air travel may result in hypoxia in patients with respiratory disease. However, little information exists on the oxygen requirements of infants with respiratory disease planning to fly. A study was undertaken to identify the clinical factors predictive of an in-flight oxygen requirement from a retrospective review of hypoxia challenge tests (inhalation of 14–15% oxygen for 20 minutes) in infants referred for fitness to fly assessment. Methods: Data from 47 infants (median corrected age 1.4 months) with a history of neonatal lung disease but not receiving supplemental oxygen at the time of hypoxia testing are reported. The neonatal and current clinical information of the infants were analysed in terms of their ability to predict the hypoxia test results. Results: Thirty eight infants (81%) desaturated below 85% and warranted prescription of supplemental in-flight oxygen. Baseline oxygen saturation was >95% in all infants. Age at the time of the hypoxia test, either postmenstrual or corrected, significantly predicted the outcome of the hypoxia test (odds ratio 0.82; 95% confidence intervals 0.62 to 0.95; p = 0.005). Children passing the hypoxia test were significantly older than those requiring in-flight oxygen (median corrected age (10–90th centiles) 12.7 (3.0–43.4) v 0 (−0.9–10.9) months; p<0.0001). Conclusions: A high proportion of ex-preterm infants not currently requiring supplemental oxygen referred for fitness-to-fly assessment and less than 12 months corrected age are at a high risk of requiring in-flight oxygen. Referral of this patient group for fitness to fly assessment including a hypoxia test may be indicated.